Perinatal Palliative Care: A qualitative study evaluating the perspectives of pregnancy counselors - Flaig, Franziska (Palliat Med, 2019)
BACKGROUND: A prenatal diagnosis of a life-limiting disease raises complex ethical, emotional, and medical issues. Studies suggest that 40%–85% of parents decide to continue the pregnancy if given the option of Perinatal Palliative Care. However, structured Perinatal Palliative Care programs are missing in many European countries. In Germany, parents have the right to free psychosocial support from pregnancy counseling services after the prenatal diagnosis of a life-limiting disease. AIM: We aimed to investigate whether German professional pregnancy counselors perceive the need for structured Perinatal Palliative Care and if so, how it should be conceived. DESIGN: This is a qualitative interview study with purposeful sampling. The interviews were analyzed with the coding method of Saldaña. SETTING/PARTICIPANTS: A total of 10 professionals from three different pregnancy counseling services participated in the study. RESULTS: The main topics raised by the professionals were as follows: (1) counseling and parental support during the decision-making process; (2) fragmented or missing support infrastructure for parents; and (3) challenges, hesitations, and barriers, particularly from the different stakeholders, regarding a Perinatal Palliative Care framework. They highlighted the importance of the integration of Perinatal Palliative Care in existing structures, a multi-professional approach, continuous coordination of care and education for all healthcare providers involved. CONCLUSION: A structured Perinatal Palliative Care program is considered as necessary by the pregnancy counselors. Future research should focus on (1) needs reported by concerned parents; (2) attitude and role of all healthcare providers involved; (3) strategies to include stakeholders in the development of Perinatal Palliative Care networks; and (4) outcome parameters for evaluation of Perinatal Palliative Care frameworks.